FACTORS ASSOCIATED WITH STUNTING AMONG TODDLERS AGED 6-24 MONTHS IN TANIMULYA VILLAGE, WEST BANDUNG DISTRICT: Faktor-Faktor yang Berhubungan dengan Kejadian Stunting di Desa Tanimulya Kabupaten Bandung Barat - Utami Ainunnisa, Rista; Kumalasari, Isti; Astuti, Widya; Rahayu Fitrianingsih, Asti Dewi; Septia Rosdiana, Delita (Universitas Airlangga, 2026)
Background: Stunting is a public health issue that remains a serious concern in Indonesia, including in West Bandung Regency, where the prevalence was 26.90% in 2022. This condition not only reflects physical growth disorders but also poses risks to children's cognitive development and future productivity. Purpose: This study aims to identify factors associated with stunting in toddlers in Tanimulya Village, West Bandung Regency. Methods: A cross-sectional study was conducted involving 83 toddlers and their parents selected through cluster random sampling. The study included children aged 6–24 months living in Tanimulya Village, excluding those with genetic disorders or chronic illnesses. Data were collected using questionnaires, WHO-standard anthropometric measurements, and 24-hour food recall, and analyzed using multivariate logistic regression with SPSS 21. Results: Of 83 toddlers, 43 were classified as stunted. Further analysis revealed that protein intake (OR: 5.14), parental role (OR: 0.35), and history of infection (OR: 0.47) were significantly associated with stunting. Multivariate analysis identified protein intake as the dominant factor influencing stunting among toddlers. Conclusion: These findings indicate that stunting prevention efforts should focus on nutrition education for families, increased parental involvement in childcare, and regular monitoring of child growth.